Comparative Study of Autologous Radiocephalic and Brachiocephalic Arteriovenous Fistula in Patients with End Stage Renal Disease - Magar, Deepak Thapa; Shrestha, Kiran; Chapagain, Dinesh; Shrestha, Kumar; Thapa, Sara (Journal of Nepalgunj Medical College, 2020)
Introduction: End-stage renal disease requires treatment with dialysis or renal transplantation. For the dialysis, autologous radiocephalic (RC) or brachiocephalic (BC) arteriovenous fistula (AVF) is the better option for vascular access for hemodialysis. Aims: The aim of this study is to find out the outcome between RC AVF and BC AVF. Methods: This is the retrospective study, conducted for the period of 24 months from September 2017 to September 2019 in the department of Cardiothoracic and Vascular Surgery of Bir Hospital, Nepal. RC and BC AVF were created for the assess of hemodialysis. Outcome and different complications were taken into consideration. Results: The total number of patients included in this study was 400. The overall failure rate of autologous AV fistula was 12.75%. Out of these, the failure rate was more in RC AV fistula group, 34 (17%) than in BC AV fistula group, 17 (8.5%). The most common complication was bleeding in both groups having an overall rate of 39 (9.75%). The limb edema was more common in BC AV fistula group 16 (8.0%) then in RC AV fistula group 7(3.5%). The overall infection rate was 4.5%. Overall patency rate was 87.25%. Conclusion: Autologous RC AVF and BC AVF are the choices for vascular access for hemodialysis in patients with end-stage renal disease. BC AVF has a better patency rate than RC AVF but with the slight higher risk of complications.